2015
DOI: 10.1177/0145445515615354
|View full text |Cite
|
Sign up to set email alerts
|

Internalized HIV Stigma and Mindfulness

Abstract: Rates of both traumatic event exposure and posttraumatic stress disorder (PTSD; 22%-54%) are disproportionately elevated among people living with HIV/AIDS (PLHA). Trauma and related psychopathology significantly affect quality of life and disease management in this patient population. The current study examined associations between internalized HIV stigma, mindfulness skills, and the severity of PTSD symptoms in trauma-exposed PLHA. Participants included 137 PLHA (14.6% female; Mage = 48.94, SD = 8.89) who rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Other authors have similarly reported that benefit finding provided greater resilience from the negative effects of stigma and promoted psychological growth in cancer survivors 6,38 . This is highly relevant to HNC survivors, as internalised stigma has been widely demonstrated in this population 6 and mindfulness‐based interventions may reduce distress as they have been shown to do in other stigmatised populations, for example, people living with HIV/AIDS 39 …”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Other authors have similarly reported that benefit finding provided greater resilience from the negative effects of stigma and promoted psychological growth in cancer survivors 6,38 . This is highly relevant to HNC survivors, as internalised stigma has been widely demonstrated in this population 6 and mindfulness‐based interventions may reduce distress as they have been shown to do in other stigmatised populations, for example, people living with HIV/AIDS 39 …”
Section: Discussionmentioning
confidence: 86%
“…6,38 This is highly relevant to HNC survivors, as internalised stigma has been widely demonstrated in this population 6 and mindfulness-based interventions may reduce distress as they have been shown to do in other stigmatised populations, for example, people living with HIV/AIDS. 39 Work was important to many participants who cited financial, social and identity related reasons for wanting to return to work.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, instead of avoiding or denying such experiences, trait mindfulness teaches individuals to cope with stressful life events by adopting an attitude of self-compassion and nonjudgment towards their own thoughts and emotions [65]. Other studies found that certain facets of mindfulness such as acting with awareness and nonreactivity, moderate health outcomes [66,67]. To the authors' knowledge, no published study has examined trait mindfulness as a moderator of the association between ETE, trauma symptomatology, and craving.…”
Section: Trait Mindfulness As a Moderatormentioning
confidence: 99%
“…Mindfulness is inversely related to anxiety, experiential avoidance, distress and uncertainty, external stimulus reactivity (poorer executive control), and persistence of negative affect [70,71]. Mindfulness programs can improve coping and resiliency in specific conditions including quality of life in patients with multiple sclerosis [72], depression and anxiety in patients with cancer [73], and specifically in trauma-exposed individuals with human immunodeficiency virus (HIV), can reduce PTSD symptoms [74]. …”
Section: Mindfulnessmentioning
confidence: 99%